Jurnal Hasil Penciptaan Karya Pakeliran Teater Karnayana - Putra Dananjaya, Esa; Adhisantika, Sang Nyoman Gede; Wicaksandita, I Dewa Ketut; Cempaka Dewi, Ni Luh Ayu (JURNAL DAMAR PEDALANGAN, 2025)
This artistic research explores the creation of Karnayana, a Balinese shadow puppet theater (teater pakeliran) that reinterprets the epic figure Karna from the Mahabharata as a locus of existential reflection. The study responds to the contemporary challenges of preserving traditional wayang in the context of globalization, shifting audience interests, and the demands of academic innovation under the Merdeka Belajar–Kampus Merdeka (MBKM) program. Employing the methodological framework of Catur Datu Kawya (Pandulame, Adicita–Adirasa, Sranasasmaya, Gunatama) developed by I Nyoman Sedana, the creative process integrates imagination, philosophical value, artistic devices, and performative skill into a coherent dramaturgy. The narrative highlights Karna’s dilemmas of loyalty, honor, and tragic destiny, realized through three main acts—his encounter with Kunti, the rejection at Drupadi’s contest, and his death in the Bharatayudha war—visualized by silhouettes, gamelan–digital compositions, vocal expressions, and lighting design. The findings demonstrate that Karnayana contributes not only as an innovative performance model that synthesizes tradition and modern theater, but also as an academic discourse that affirms the relevance of philosophical-humanist values in contemporary art. Thus, the work establishes a dual contribution: revitalizing the artistic grammar of Balinese wayang and offering a methodological reference for artistic creation within higher education.